2008
DOI: 10.1007/s10611-008-9178-5
|View full text |Cite
|
Sign up to set email alerts
|

Torn between two targets: German police officers talk about the use of force

Abstract: Considering earlier research into police use of force as well as the judicial and practical frame of police work in Germany, the article presents the results of an empirical study on the individual and collective legitimization of the use of force by German police officers. There are numerous justifications for the use of force expressed by focus group participants in eight German Federal States who were responding to a hypothesized scenario. In the discussions observed within the groups, reference is first ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Yet, the interpretation of Bcannot be achieved in any other way^varies. As Klukkert et al (2009) indicated, emotional cognitions centered around the fear of losing authority and the fear of escalation may trigger aggression towards initially non-compliant citizens. Though still in line with legal and institutional guidelines, exhibiting aggression too early in police-citizen encounters may impose costs for the officer at a later point, for instance through an increased risk to the officer's physical integrity following a suspect resisting arrest (Reisig et al 2004;Sherman 1993;Tyler and Huo 2002;Wolfe 2011).…”
Section: Self-control and Aggressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, the interpretation of Bcannot be achieved in any other way^varies. As Klukkert et al (2009) indicated, emotional cognitions centered around the fear of losing authority and the fear of escalation may trigger aggression towards initially non-compliant citizens. Though still in line with legal and institutional guidelines, exhibiting aggression too early in police-citizen encounters may impose costs for the officer at a later point, for instance through an increased risk to the officer's physical integrity following a suspect resisting arrest (Reisig et al 2004;Sherman 1993;Tyler and Huo 2002;Wolfe 2011).…”
Section: Self-control and Aggressionmentioning
confidence: 99%
“…To date, research has yet to address the potential relationship between self-control failure and use of force. Klukkert et al (2009) investigated the motivation of German police officers to use force and provided first empirical insight: in contrast with prescribed behavior that follows legal and institutional guidelines (i.e., reflecting top-down-driven behavior), the routine behavioral conflict situations of police work are often emotionally driven. The researchers concluded that Bthe more the officers are drawn into the whirlpool of conflicts between maintaining authority on the one and the fear of escalation on the other hand, the more their actions will be determined by emotions and the higher the probability that legal guidelines will be ignored and that a violent response will serve as a mechanism to resolve the conflict^ (p. 199).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the ability to achieve compliance, use of force generally results in merely temporary compliance and may ultimately lead to disrespect and violence on the part of the subject (Reisig, McCluskey, Mastrofski, & Terrill, 2004;Sherman, 1993;Tyler & Huo, 2002;Wolfe, 2011). A study with German police officers investigating the motivation to use force provided first empirical insights on that matter (Klukkert, Ohlemacher, & Feltes, 2009): Results showed that routine situations of behavioral conflict experienced by police officers are often emotionally driven, in contrast to prescribed behavior, which follows legal and institutional guidelines. A study with German police officers investigating the motivation to use force provided first empirical insights on that matter (Klukkert, Ohlemacher, & Feltes, 2009): Results showed that routine situations of behavioral conflict experienced by police officers are often emotionally driven, in contrast to prescribed behavior, which follows legal and institutional guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the context, a cessation of inhibition may sometimes be functional (Reynolds & McCrea, 2016). As Klukkert et al (2009) indicated, emotional cognitions concerned the fear of losing authority, and the fear of escalation may trigger aggression towards initially noncompliant citizens. Yet, the interpretation of 'cannot be achieved in any other way' varies.…”
Section: Introductionmentioning
confidence: 99%
“…Focus group research is regularly applied in qualitative criminological research. For example, it is used to study the ideas and perceptions of professionals working in the criminological field (see, among others, Douglas & Cuskelly, 2012;Kaye et al 2014), ideas and perceptions of the general public and young people on crime and the justice system (Boda & Szabo, 2011;Dirikx et al 2012), and perceptions of professionals on sensitive topics such as police peer retaliation (Cancino & Enriquez, 2004) and the use of force by the police (Klukkert et al 2009). It has been regularly applied to study sensitive topics such as abuse, violence, drug use and sex work and the populations -victims, offenders and prisoners -involved (see among others Wachholz & Miedema, 2000;Surratt et al 2004;Garcia & Lane 2012).…”
mentioning
confidence: 99%